Morgan reunion set (Raton Range Raton, New Mexico, 1984)
Newspaper Article on family reunion of Mr. and Mrs. J. Manley Morgan.
Master list item #: 11
File location is in the Raton File Cabinet
Keywords: Morgan, J. Manley; Morgan, Ruth; Graham, Christine; Graham, Britton; Graham, Nancy; Hayes, Reba; Caldwekk, Martha Jane; Gumm, Clark; Graham, Peyton; Morgan, Georgia; Morgan, John; Feldman, John E. Jr; Feldman, George; Strait, Nancy Ruth; Allen, Manley; King, Virginia; Hays, Judy; Mutcheler, Sue; Morgan, Jim; Morgan, George; Morgan, John C; Morgan, Fred; Morgan, Frank; Morgan, Calvin; Durand, Sally; Sands Motel; Local History; Biography; Life and Customs; Family; Reunion; Raton, New Mexico